NILAI SIKAP BEKERJA DALAM PERIBAHASA INGGRIS SEHUBUNGAN DENGAN KUDA DAN PADANANNYA DALAM BAHASA INDONESIA - N.K. Mirahayuni (Universitas 17 Agustus 1945 Surabaya, 2016)
Abstract. Interests in proverbs has emerged with the fact that proverbs has been used worldwide to express wisdom of proper attitudes and behaviour when interacting in different societies. This paper is part of an ongoing study on values in English and Indonesian proverbs related with horse, cow, bufallo and donkey. These four animals are chosen as the subject of proverbs study as they are traditionally used as means of transports and other purposes. Proverbs are generally identified from its brief and memorable words or sentences that express truth and reality and in many ocassion express advice. Like other symbolic languages, proverbs involve language style and symbols that are used to describe people or something through, among others, comparison that describe something of someone. Proverbs contain daily experiences and general observation that are expressed in a fixed and effective language forms that they are memorable and are ready to use as an effective rhetorical device in both oral and written language (Mieder 2004). Proverbs are unique in how wisdom and acceptable attitudes in the community are communicated to younger generation. Proverbs express an awareness of human condition and weakness that voices of advice that are expressed in this special language may be sounded with clarity, humour, wit and insights (Barajaz, 2010). The paper reports the descriptive qualitative study on English proverbs related to horse and their equivalence or similar functions in Indonesian proverbs. The data of the study are collected from various printed and electronic sources of English and Indonesian proverbs. The study found that a number of good wisdom and advise related to work attitudes are taught and transmitted using horse as the keywords. In the context of English language learning for Indonesian students, one language aspects that are often difficult for learners are the socio-cultural values wrapped in the daily language expressions. This includes proverbs that are closely related to the thought patterns and acceptable values in the language users, especially in English. More information on English proverbs may help them achiever better understanding of the socio-cultural aspect of English.Keywords: English proverbs on horse, socio-cultural values, Indonesian equivalence